A descriptive study on standalone risk management committee adoption among the top 50 Malaysian firms / Naqiah Awang... [et al.] - Awang, Naqiah; Hussin, Nur Syafiqah; Razali, Fatin Adilah; Abu Talib, Shafinaz Lyana (2021)
In a modern business environment, business is considered more fragile as compared to the traditional business setting due to technology sophistication and global market uncertainty. Firms cannot run away from managing unique and complicated risk issues when exploring greater opportunities for a higher return in a competitive market. Realizing this, the Securities Commission of Malaysia had encouraged large, listed firms to form a separated Risk Management Committee to ensure better anticipation and responsiveness towards risk management issues. However, this practice is still voluntary among Malaysian listed firms most probably to allow internal coordination among different business atmospheres. Hence, this paper aims to describe the adoption level of the best practices to establish a standalone Risk Management Committee among the top 50 largest listed firms in Bursa Malaysia. Given the issuance of the Malaysian Code of Corporate Governance 2017 before the attributes of the Risk Management Committee were further explored. Secondary data were adopted, and information was gathered from the firms' annual reports in 2018 and 2019. It is available on the Bursa Malaysia website and each sampled firm's website. The results revealed that more than half of Malaysian listed firms had taken the initiative to establish a standalone Risk Management Committee following the best practices recommended by the Malaysian Code of Corporate Governance 2017. However, the composition of Risk Management Committee members is heavily tied to the Audit Committee. This current study provides insight into the risk governance structure among Malaysian listed firms after issuing the Malaysian Code of Corporate Governance 2017.